Complete Genome Sequence of Klebsiella pneumoniae Strain ATCC 43816 - Budnick, James A. (Microbiol Resour Announc, 2021)
Klebsiella pneumoniae is a member of Enterobacteriaceae that causes a multitude of infections in compromised and healthy individuals. The rise of hypervirulent and multiple-drug-resistant K. pneumoniae strains has made this organism a global health threat. Here, we report the complete genome sequence of K. pneumoniae strain ATCC 43816.